Pemetaan Atribut Sensori Kopi Kobura Berdasarkan Perbedaan Cara Panen dan Pengolahan di Tingkat Petani - Enny Randriani; Elsera Br Tarigan; Edi Wardiana (Jurnal Tanaman Industri dan Penyegar, 2021)
In general, Kobura coffee farmers in South Ogan Komering Ulu (OKU) harvest coffee with the criteria of red fruit and a mixture of red and green, while the processing method is a dry process. However, the sensory attributes of these activities are not yet known. This study aims to map the sensory qualities of Kobura coffee at the farmer level based on differences in harvesting and processing methods. The research was carried out in Banding Agung District, South OKU Regency, and the Coffee and Cocoa Bioindustry Laboratory, Balittri, Sukabumi, from March to December 2019. The design used was a completely randomized design with 3 treatment factors and two replications. The first factor was three clones of Kobura coffee (Kobura 1, 2, 3), the second factor was two harvesting methods (red and mix of red + green fruit), and the third factor is two processing methods (dry and wet). The variable observed were the sensory attributes analyzed by multivariate analysis of variance, principal component analysis, cluster analysis, and path analysis. The results showed that the harvesting and processing methods of Kobura coffee at the farmer level in South OKU did not significantly affect the sensory. Furthermore, each cluster's harvesting and processing methods were evenly distributed because the proportion between red and green fruit was not clearly identified in the mixed fruit harvest. Superior genetic and optimal altitude factors make Kobura coffee categorized into Fine Robusta with a final score of 81.13-85.75. The final score is directly and dominantly influenced by mouthfeel (body), flavor, overall, and fragrance, respectively.